Statin Use Reduces Prostate Cancer All-Cause Mortality. Issue 39 (September 2015) - Sun, Li-Min; Lin, Ming-Chia; Lin, Cheng-Li; Chang, Shih-Ni; Liang, Ji-An; Lin, I-Ching; Kao, Chia-Hung; Shiota., Masaki
<x xml:space="preserve">Abstract</x> Abstract Studies have suggested that statin use is related to cancer risk and prostate cancer mortality. We conducted a population-based cohort study to determine whether using statins in prostate cancer patients is associated with reduced all-cause mortality rates. Data were obtained from the Taiwan National Health Insurance Research Database. The study cohort comprised 5179 patients diagnosed with prostate cancer who used statins for at least 6 months between January 1, 1998 and December 31, 2010. To form a comparison group, each patient was randomly frequency-matched (according to age and index date) with a prostate cancer patient who did not use any type of statin-based drugs during the study period. The study endpoint was mortality. The hazard ratio (HR) and 95% confidence interval (CI) were estimated using Cox regression models. Among prostate cancer patients, statin use was associated with significantly decreased all-cause mortality (adjusted HR = 0.65; 95% CI = 0.60–0.71). This phenomenon was observed among various types of statin, age groups, and treatment methods. Analyzing the defined daily dose of statins indicated that both low- and high-dose groups exhibited significantly decreased death rates compared with nonusers, suggesting a dose–response relationship. The results of this population-based cohort study suggest that using statins reduces all-cause mortality among prostate cancer patients, and a dose–response relationship may exist.